Effectiveness of the Bacillus Calmette-Guerin vaccine in an Indonesian population with D543N NRAMP1 polymorphism - Ikhwanuliman Putera; Trevino Aristarkus Pakasi; Ikrar Syahmar; Aulia Akbar Bramantyo; Elvina Karyadi; Ani Melani; Edhyana Sahiratmadja (Journal of Infection in Developing Countries)
Introduction: Bacille Calmette-Guerin (BCG) vaccination remains a routine immunization in primary care in tuberculosis (TB)-endemic areas, though several studies found that its efficacy was inconclusive. Natural resistance-asociated machrophage protein 1 (NRAMP1) polymorphism has been shown to result in higher susceptibility to TB. Information on genetic susceptibility in populations will be useful in planning the application of the BCG vaccine. The present study explored BCG efficacy in a rural Timor population with specific NRAMP1 polymorphism in a TB-endemic region of eastern Indonesia. Methodology: A case-control study with 64 newly diagnosed pulmonary TB patients and 65 healthy controls was performed. BCG scars were examined by a physician. NRAMP1 polymorphism was evaluated using molecular methods. Results: Half of the subjects (65; 50.4%) had a clear presenting BCG scar on the upper arm, suggesting a successful BCG vaccination. Among the subjects, D543N NRAMP1 polymorphism, history of contact with TB patients, and not having a clear BCG scar on the upper arm tended to be significantly association with active TB. The significant differences were more profound when subjects were divided based on presenting BCG scar. Subjects without clear BCG scars had significant association with developing TB disease (p = 0.014). In multivariate analysis, history of previous contact with TB patients and unclear presenting BCG scar were associated with active TB (OR 9.2; 2.0–43.8 95% CI, OR 4.8; 2.1–11.0 95% CI, respectively). Conclusions: BCG vaccination in our population was effective for TB protection, especially in highly endemic areas of TB, regardless genetic susceptibility.